2012
DOI: 10.1080/14786419.2010.551643
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity ofGentiana striataMaxim.

Abstract: The anti-inflammatory activity and the mechanism of action of Gentiana striata Maxim. has been investigated. The most active phase, the ethyl acetate extract of Gentiana striata Maxim. (EGS), displayed potent inhibitory activity on feet oedema of rheumatoid arthritis (RA) inflicted rats. This anti-inflammatory activity might be partly based on the notable reduction of prostaglandin E2 (PGE₂) and nitric oxide (NO) levels. Six further compounds isolated from EGS have previously been reported as having anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…There was a marked decrease in the PGE 2 and NO levels. Six compounds including two iridoids, loganin ( 8 ) and sweroside ( 9 ), was isolated from this extract [ 94 ].…”
Section: Iridoid Chemistry and Researched Anti-inflammatory Iridoid-cmentioning
confidence: 99%
“…There was a marked decrease in the PGE 2 and NO levels. Six compounds including two iridoids, loganin ( 8 ) and sweroside ( 9 ), was isolated from this extract [ 94 ].…”
Section: Iridoid Chemistry and Researched Anti-inflammatory Iridoid-cmentioning
confidence: 99%
“…Thus, there may be great potential for the prevention and treatment of inflammation to suppress the signaling molecules of iNOS expression [9]. Previous reports have shown that the Gentiana species possesses anti-inflammatory activity [10][11][12][13][14]. Animal experiments showed that gentiopicroside possesses anti-inflammatory effects on acute and chronic inflammatory reactions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Tectochrysin (TEC), one of the major flavonoids of propolis, [ 27,28 ] is also present in various other natural sources, such as the plant Alpinia oxyphylla , [ 29 ] Kaempferia parviflora , [ 30 ] Muntingia calabura , [ 31 ] and Carya genus. [ 32 ] Previous pharmacological studies have shown that TEC possesses antioxidant, [ 33 ] anticancer, [ 26,34 ] antidiarrheal, [ 35 ] anti‐ Leishmania amazonensis amastigotes, [ 36 ] trypanocidal, [ 37 ] and aryl hydrocarbon receptor ligand [ 38 ] activities. Furthermore, it was also found that TEC has the ability to promote adipocyte differentiation and stimulate adipogenesis.…”
Section: Introductionmentioning
confidence: 99%